Chile : institutions and policies underpinning stability and growth - Kalter, Eliot; International Monetary Fund. (Washington, DC : International Monetary Fund, 2004)
The selected materials presented in this occasional paper reviewed the institutions and policies adopted by Chile in the past two decades that have enabled it to reduce its vulnerabilities while benefiting from the ongoing process of globalization. These collections could provide a unified source of lessons for countries that, like Chile, are committed to undertake sustainable improvements to their economic policies and institutions. It also includes some forward looking suggestions.
Overview / Eliot Kalter -- Role of institutions in Chile / Marco A. Espinosa-Vega and Steven Phillips -- Chile's macroeconomic policy framework / Steven Phillips and Marco A. Espinosa-Vega -- Capital markets and corporate financing : recent developments / Rodolfo Luzio -- Chilean banking system: recent developments / Marco A. Espinosa-Vega -- Assessment of Chile's external position / Rodolfo Luzio -- Public sector finances: balance sheets, financing needs, and sustainability / Steven Phillips -- Export specialization and economic growth / Mauricio Villafuerte.
Includes bibliographical references.
nmn 6/06/13
Loans
Keywords: Chile -- Economic policy; Chile -- Economic conditions -- 1988-; Capital market -- Chile; Banks and banking -- Chile